Islamic Female Clerics’ Preaching on the Discourse of Woman’s Body, Sexuality and Domestication: A Study through Transitivity and Appraisal Analysis - Leiliyanti, Eva; Munir, Hazalia Zahra; Awaliyah, Wita (UIN Salatiga, 2022)
This text-oriented discourse analysis aims to evaluate and compare the language voiced by the two Islamic female clerics’ (Ustazah Aisah Dahlan and Mamah Dedeh) in their preaching as well as their stances towards the Discourse of Muslim Woman’s Body, Sexuality and Domestication posted on their affiliated Youtube accounts during this Covid-19 pandemic. The data (two video transcripts with the duration 09 minutes 04 seconds and 42 minutes and 54 seconds, respectively) were taken based on stratified purposeful sampling. Using transitivity system (ideational metafunction of language) postulated by M.A.K. Halliday(2014) and language evaluation theory (interpersonal metafunction of language) developed by Martin and White (2005), it was found that Aisah Dahlan’s preaching was dominated by attributive relational process and positive judgment in heteroglossic expressions to justify Muslim men’s attitudes and behaviors, whereas negative judgment in force expressions were deployed in discussing the Muslim woman’s body, sexuality, and domestication discourse. On the contrary, Mamah Dedeh’s preaching was dominated by the material process and positive judgement of sanction which indicates that husband and wife share equal responsibility in the household.Keywords: Ustazah, Text-Oriented Discourse Analysis, Muslim Woman’s Body, Islamic views on Sexuality, Domestication of woman, Transitivity analysis, appraisal analysis